MODELS AND TECHNOLOGIES FOR ADOLESCENT DEVIANT BEHAVIOR CORRECTION WITH THE USE OF ART EDUCATION AND CULTURAL STUDIES (CASE OF THE LENINGRAD REGION) - Mikhalchenkova, Natalya; Bolshakov, Sergey; Bolshakova, Julia; Kulikova, Nadezhda; Krasilnikova, Svetlana (Revista Inclusiones, 2020)
Based on the results of sociological and comprehensive studies, the article analyzes the problems of using the methods of art education and cultural studies in the prevention and correction of adolescent deviant behavior. The implemented tools of sociological assessment allowed the authors to identify a set of tasks related to selecting the most demanded and effective instruments for adolescent deviant behavior prevention and correction. The study summarizes the existing pedagogical experience of the implementation of artistic and creative programs in educational institutions. The pedagogical potential of art education and cultural studies programs in correctional work is identified. The results of the study demonstrate that despite the demand for such programs, educational organizations experience a deficit of resources necessary for their comprehensive development and implementation. The study results allow the authors to identify not only the types of deviant behavior of students of educational institutions but also the predominant types of student deviant behavior manifestation (according to study respondents): accentuated behavior, inadequate behavior, auto-aggressive behavior, etc. Sociological survey results make it possible to establish the interest not only on the part of parents who demonstrate their initiative in placing an adolescent in various institutions, but also adolescents themselves who are often aware of the consequences of their destructive behavior (more than 30% of respondents). The article highlights the importanceof educational institutions transitioning to the system of project management of the processes for the organization of social services provision and promotion in the region. Most of the study respondents demonstrated an element of feedback and educational program assessment in the form of effectiveness monitoring.